2022
DOI: 10.1186/s41747-021-00254-w
|View full text |Cite
|
Sign up to set email alerts
|

Vector-field dynamic x-ray (VF-DXR) using optical flow method in patients with chronic obstructive pulmonary disease

Abstract: Background We assessed the difference in lung motion during inspiration/expiration between chronic obstructive pulmonary disease (COPD) patients and healthy volunteers using vector-field dynamic x-ray (VF-DXR) with optical flow method (OFM). Methods We enrolled 36 COPD patients and 47 healthy volunteers, classified according to pulmonary function into: normal, COPD mild, and COPD severe. Contrast gradient was obtained from sequential dynamic x-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Healthy volunteers took several tidal breaths followed by one forced breath, while COPD patients took tidal breaths and a forced breath separately. Imaging parameters for DDR were almost the same as the previous reports [16] , [18] : tube voltage, 100 kV; tube current, 50 mA; pulse duration of pulsed X-ray, 1.6 ms; source-to-image distance, 2 m; additional filter, 0.5 mm Al plus 0.1 mm Cu. The additional filter was used to remove soft X-rays.…”
Section: Methodsmentioning
confidence: 84%
See 4 more Smart Citations
“…Healthy volunteers took several tidal breaths followed by one forced breath, while COPD patients took tidal breaths and a forced breath separately. Imaging parameters for DDR were almost the same as the previous reports [16] , [18] : tube voltage, 100 kV; tube current, 50 mA; pulse duration of pulsed X-ray, 1.6 ms; source-to-image distance, 2 m; additional filter, 0.5 mm Al plus 0.1 mm Cu. The additional filter was used to remove soft X-rays.…”
Section: Methodsmentioning
confidence: 84%
“…The multivariate linear regression analysis revealed significant differences in the SImax/SImin between the severe COPD and the normal groups, as well as between the severe COPD and the mild groups. While multiple studies to date have demonstrated the utility of quantitative DDR markers in assessing pulmonary function in COPD patients [10] , [12] , [14] , [16] , [17] , [18] , [20] , [23] , this is the first report to focus on the signal intensity changes of the entire lung fields on DDR images in COPD patients and investigate the correlation with PFT parameters and the differences by disease severity.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations